1994
DOI: 10.4327/jsnfs.47.93
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Serum Carotenoids after Continual Ingestion of Tomato Juice.

Abstract: continual ingestion of tomato juice. The change in the level of cholesterol during this period was investigated simultaneously. Sixty-five female students were divided into 4 groups. They ingested either 1, 2 or 3 cans of tomato juice per day and the control group received a can of apple juice per day for 4 weeks. The lycopene level in serum showed a significant increase following the ingestion of tomato juice. In the case of subjects ingesting 2 or 3 cans daily, the level in serum increased to over three time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…The 500 mg/day dose of vitamin C that was chosen was comparable with the estimated daily intake of 300 mg vitamin C in the tomato juice supplement. The volume of the tomato juice supplement was similar to volumes used previously to increase plasma lycopene levels (12). During the initial 4 weeks of the study, all patients received the placebo capsule and then proceeded to their assigned supplement for the following 4 weeks.…”
Section: Study Design and Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The 500 mg/day dose of vitamin C that was chosen was comparable with the estimated daily intake of 300 mg vitamin C in the tomato juice supplement. The volume of the tomato juice supplement was similar to volumes used previously to increase plasma lycopene levels (12). During the initial 4 weeks of the study, all patients received the placebo capsule and then proceeded to their assigned supplement for the following 4 weeks.…”
Section: Study Design and Protocolmentioning
confidence: 99%
“…Lycopene, a major carotenoid in human plasma, also inhibits the oxidative modification of isolated LDL (11). Tomato products in the diet are the Antioxidants and LDL oxidation in diabetes main source of plasma lycopene, and supplementation with tomato juice increases plasma lycopene levels in healthy subjects (12). Vitamin C is usually added to commercial tomato juices and in the aqueous milieu, can also protect plasma lipids and LDL from oxidative damage.…”
mentioning
confidence: 99%
“…Although comparing this study with other carotenoid bioavailability studies reported in the literature (Micozzi et al, 1992;Sakamoto et al, 1994;Yeum et al, 1998;Muller et al, 1999;Holloway et al, 2000;Lee et al, 2000;Pellegrini et al, 2000) and summarized in Table 3, it was evident that FSMP contained a good relative amount of carotenoids and fats. In fact, in many studies, absorption efficiency was shown to decrease as the amount of carotenoids increased (Erdman et al, 1993;Parker, 1996;Furr and Clark, 1997;Castenmiller and West, 1998;Van den Berg et al, 2000).…”
Section: Carotenoid Bioavailability Studiesmentioning
confidence: 89%
“…Details of their estimation have already been reported. 12) Tomato juice used in the present study, including the commercially manufactured product, contained no extra additives except distilled water. For experiments, the prepared tomato juice was diluted again with the same amount of distilled water twice a week just before the use, to a quarter (the concentration of lycopene being 25 ppm) of the commercially available concentration, and given in lightopaque bottles.…”
Section: Methodsmentioning
confidence: 99%